2005
DOI: 10.1159/000082635
|View full text |Cite
|
Sign up to set email alerts
|

High Homeopathic Potencies Are Different from Potentized Solvent when Investigated with the REDEM Technology

Abstract: Objective: To determine in a series of randomized blinded experiments using the REDEM technology whether differences between high homeopathic potencies and similarly potentized solvent can be detected. Design and Analysis: A REDEM device was employed as a black box. Samples were measured in a capacitor that was connected to 60 individual oscillator circuits at frequencies between 250 and 930 KHz; their oscillation damping was recorded. In two experiments (3 and 4 replications) stable differences between a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Further potentising or another day of material contact produced no significant changes. The experiments were performed to confirm and quantify the expected contamination, to determine what type of controls equalled homeopathic remedies regarding the concentration of trace elements, and thus to establish appropriate controls for further investigations [24,29]. Our equipment and materials were the same as used in standard pharmaceutical production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further potentising or another day of material contact produced no significant changes. The experiments were performed to confirm and quantify the expected contamination, to determine what type of controls equalled homeopathic remedies regarding the concentration of trace elements, and thus to establish appropriate controls for further investigations [24,29]. Our equipment and materials were the same as used in standard pharmaceutical production.…”
Section: Discussionmentioning
confidence: 99%
“…One of our investigators (CW) had repeatedly found differences between mother tincture potencies and potentised ABD using a black box device. The investigated samples were of exactly the same kind as the samples of the present analysis regarding ABD source, used materials, preparation, and sample ages [24,29]. The output of the device was generally higher in samples similar to those showing higher contamination in the ICP-MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…If the problem is couched in physical and not merely in chemical terms, it is very likely that any such explanation must necessarily take into account the sensitivity of living systems to small energies like those carried by EM fields. 109,110 In this context, the emerging bioelectromagnetic paradigm will have an important role because it re-evaluates an important form of long-range communication, not only at intermolecular but also at supramolecular levels of organization of biological systems.…”
Section: Biophysical Interactionsmentioning
confidence: 99%
“…Given these, solitary remedy-control differences being adjacent to differences for more than one remedy are very unlikely to identify a remedy, therefore we did not calculate differences between experiments. 44 .In this paper we show that various chemical stressors at concentrations that do not exert any effect on tolerance development or hsp synthesis in control cells are able to stimulate these parameters when applied to heat-treated cells. In previous work we showed that under specific circumstances a low dose of a stressor is able to exert a stimulatory action in cells that had been previously treated with a high dose of the same agent.…”
Section: Discussionmentioning
confidence: 72%